Translation and validation of the Bahasa Malaysia version of the Patient-Specific Functional Scale (PSFS)/ Akehsan Dahlan, Muhammad Danial Mohd Yasin, Zati Izni Achmy - Dahlan, Akehsan; Mohd Yasin, Muhammad Danial; Achmy, Zati Izni (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Purpose This study aimed to translate and culturally validate the Patient-Specific Functional Scale (PSFS) into the Bahasa Malaysia version to the elderly with sarcopenia. Methods The PSFS underwent an established process of translation and cross-cultural adaptation from a published guideline. A total of 94 community living elderly participated in this study. The investigated psychometric properties of the PSFS-BM included concurrent validity, convergent validity, and test-retest reliability. The elderly completed the English version of PSFS and the PSFS-BM for the evaluation of the concurrent validity. The convergent validity was assessed by comparing the PSFS-BM with the Canadian Occupational Performance Measure (COPM). A two weeks interval was set to assess test-retest reliability. Results Pearson correlation coefficient of 0.97 indicated that a strong positive correlation exists between the English version of PSFS and the PSFS-BM. The Pearson correlation coefficient with the r value of 0.78 and 0.69 also reflect a strong relationship of the PSFS-BM with the COPM. The test-retest reliability was good with the intraclass correlation coefficient of 0.84. The standard error of measurement and the minimal detectable change was 0.6 and 1.4, respectively. The Bland-Altman plot indicated a good agreement between the initial test and retest scores. A strong correlation of the initial test and retest scores was also observed using the Pearson correlation coefficient. Conclusion The PSFS-BM is a valid and reliable instrument to assess the functional ability of the community living elderly with the possibilities of sarcopenia.